A Post-intentional Phenomenological Study of a Queer Identified Youth in Jamaica (Global Journal of Human-Social Science, 2023)
The paper provides an exploration of glimpses into the life of a Jamaican woman who loves women The research question this paper examines is how societal homonegativity shapes the lived experiences of a young woman who loves women in Jamaica Post-intentional phenomenology methodology was used to capture salient moments of the woman s life through written memory song lyrics and artifacts Results suggested that fear hope care and being perceived as diseased are a daily part of a woman who loves women s life There is a need to tell the stories of women who love in Jamaica to validate their lived experiences and to construct a body of knowledge on this topic Implications for this study can be used to mobilize education research community and support for students with female same-sex caregivers
Keywords: same-sex; jamaica; women; lived experience; phenomenology